Debtor-in-possession financing - Chatterjee, Sris; Dhillon, Upinder S.; Ramı́rez, Gabriel G. (Journal of Banking & Finance, 2004)
Several recent papers have documented the benefits of debtor-in-possession (DIP) financing in the restructuring of firms in Chapter 11. However, the view on benefits is not unanimous and some legal scholars have raised doubts about DIP financing's effects on debt-holders and the possibility of expropriative wealth transfers. In this paper we address this issue by analyzing both stock and bond price data for a comprehensive sample of DIP loans and find significant positive abnormal stock and bond returns at the announcement of DIP loans. Also, we do not find evidence of wealth transfers from junior to senior debt-holders. Further, we examine the DIP loan process in detail and we document important institutional features of DIP loans such as maturity, covenants, fees and interest charges. We find evidence of intense monitoring using covenants. We also find higher fees and charges associated with DIP loans. We argue that overall the results are consistent with the information processing role of financial intermediaries.